2019
DOI: 10.1371/journal.pone.0215599
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body dual-energy X-ray absorptiometry demonstrates better reliability than segmental body composition analysis in college-aged students

Abstract: Dual-energy X-ray absorptiometry (DXA) is rapidly becoming more accessible and popular as a technique to monitor body composition. The reliability of DXA has been examined extensively using a number of different methodological approaches. This study sets up to investigate the accuracy of measuring the parameters of body composition (BC) by means of the whole-body and the segmental DXA method analysis with the typical error of measurement (TEM) that allows for expressing the error in the units of measure. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…Collectively, runners demonstrated a 2.4 % increase over one year in total body BFLM compared to a 0.8 % increase in non-runners and whole-body BFLM was higher in both male and female runners compared to their non-running counterparts, but these differences were not due to differences in the upper-extremity. The likelihood that this represents real change is supported in the finding that these changes in BFLM ( > 1 kg) fall well above published whole body scan-rescan precision assessments observed in similarly sized, collegiate males (typical error of measurement (TEM) = 0.42 kg, 95 % CI = 0.36-0.50 kg) and females (TEM = 0.24 kg, 95 % CI = 0.20-0.30 kg) using the same type of DXA scanner [25]. These findings suggest that benefits in sarcopenia prevention due to competitive running are masked when examining handgrip strength, the most common upper-body index of muscular performance alone.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Collectively, runners demonstrated a 2.4 % increase over one year in total body BFLM compared to a 0.8 % increase in non-runners and whole-body BFLM was higher in both male and female runners compared to their non-running counterparts, but these differences were not due to differences in the upper-extremity. The likelihood that this represents real change is supported in the finding that these changes in BFLM ( > 1 kg) fall well above published whole body scan-rescan precision assessments observed in similarly sized, collegiate males (typical error of measurement (TEM) = 0.42 kg, 95 % CI = 0.36-0.50 kg) and females (TEM = 0.24 kg, 95 % CI = 0.20-0.30 kg) using the same type of DXA scanner [25]. These findings suggest that benefits in sarcopenia prevention due to competitive running are masked when examining handgrip strength, the most common upper-body index of muscular performance alone.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, Hart et al (2015) reported intra-tester CVs of 1.6-1.9 % and inter-tester CVs of 1.8-2.2 % for a variety of upper extremity lean mass values in professional athletes while using the same DXA model. Lastly, Kutac et al [25], again using the same DXA model to investigate retest precision of segmental analyses of lean mass, revealed nearly perfect correlational reliability and error approximations in male (TEM = 0.17 kg, 95 % CI = 0.14-0.20 kg) and female (TEM = 0.08 kg, 95 % CI = 0.07-0.10 kg college students. These studies collectively demonstrate a robust precision of whole body and segmental lean mass assessments when technicians tightly adhere to positioning procedures.…”
Section: Fatmentioning
confidence: 94%
See 1 more Smart Citation
“…Body composition and the changes it undergoes play an important role in athletes’ performance, particularly in those who are in the process of physical development as their physical abilities directly affect their performance and the risk of injuries when practicing sports modalities based on resistance, strength, power, or speed ( 1 - 4 ). It is vital, then, to count with evaluation methods of proven validity and reliability ( 3 - 5 ).…”
mentioning
confidence: 99%
“…The personnel in charge of athletes who are still developing their abilities or those that are already professionals use doubly indirect methods to measure the body composition: the data derived from measuring skin folds and the information from bioimpedance devices later used to feed prediction formulas specifically adjusted to the population for whom they were developed that may not necessarily be applicable elsewhere, as is the case of athletes from Medellín expected to become high performers ( 1 , 2 , 4 ).…”
mentioning
confidence: 99%